Study on three-dimensional multiphysics-coupled load-following operation of small lead-cooled fast reactors for grid peak shaving - Haochen Huang; Daogang Lu; Yu Liu; Yuchao Wang; Hao Ding; Danting Sui (Annals of Nuclear Energy, 2026)

Hydroxyapatite-facilitated microalgae-bacteria aggregates enable robust aeration-free nutrient removal from saline domestic wastewater - Danting Shi; Tao Liu (Water Research, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Inhalation exposure and health risks of PM2.5-associated metals in a machinery plant: Probabilistic assessment and mask protection limits - Jianchao Ma; Fan Liu; Danting Luo; Xiaohong Zheng; Sujun Leng; Nianyong Zhou; Bingyuan Li; Hua Qian (Atmospheric Pollution Research, 2026)

Non-thermal plasma-catalytic methane to methanol: Unlocking synergy through tailored nickel dispersion - Danting Peng; Yufei Ji; Yanshi Zhang; Junfei Liu; Guannan Huo; Ning Ding; Haibao Huang; Daiqi Ye; Junliang Wu (Journal of Environmental Chemical Engineering, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Co-exposure to triclosan and polystyrene nanoplastics on neurodevelopmental toxicity and gut microbiota dysbiosis in zebrafish (Danio rerio) - Danting Wang; Junying Lan; Wentong Meng; Junping Liu; Ruixue Zhou; Chunxia Chen; Li Qin; Bin Tan; Chunyan Huang (Environmental Pollution, 2025)

Seepage rate and uniformity of the stalk composite pipe for subsurface irrigation - Songmei Zai; Huanyu Wei; Xuemei Liu; Feng Wu; Linbao Liu; Danting Liu; Xin Li; Weiye Liu; Zaiyu Li (Irrigation and Drainage, 2025)
An orthogonal experiment with three factors and three levels was conducted to study the seepage rate and uniformity of stalk composite pipe (SCP) under subsurface SCP irrigation (SSI). Furthermore, to determine the best application mode for SSI, the pipeline length, irrigation volume and inner–outer diameter of the SCP were considered at a 0.4 m working pressure. The three levels corresponding to each factor were 20, 40 and 60 m; 30, 45 and 60 L m⁻¹; and 28–60, 40–80 and 50–100 mm, respectively. The results indicated that the seepage rate gradually decreased with increasing pipeline length. The pattern of the change in the seepage rate with irrigation volume was not obvious. There was a positive correlation between the seepage rate and the inner–outer diameter of the SCP. The irrigation uniformity coefficient, which was calculated based on the width of the surface wetting front, gradually decreased with increasing pipeline length. The impact patterns of irrigation volume and inner–outer diameter on irrigation uniformity were ambiguous. The seepage rate reached its maximum at the pipeline length, irrigation volume and inner–outer diameter, which were 20 m, 30 L m⁻¹ and 50–100 mm, respectively. There was the highest irrigation uniformity, with a pipeline length, irrigation volume and inner–outer diameter of the SCP of 20 m, 60 L m⁻¹ and 40–80 mm, respectively.

Bioreduction of chromate in a syngas-based membrane biofilm reactor - Chenkai Niu; Xinyu Zhao; Danting Shi; Yifeng Ying; Mengxiong Wu; Chun-Yu Lai; Jianhua Guo; Shihu Hu; Tao Liu (Journal of Hazardous Materials, 2024)

Are Mini and full-size electric vehicle adopters satisfied? An application of the regression with dummy variables - Danting Zhao; Yuandong Liu; Hong Chen (Travel Behaviour and Society, 2024)

In silico, in vitro and in vivo safety assessment of three Limosilactobacillus mucosae strains for probiotic candidates - Danting Dang; Xiaoming Liu; Haiqin Chen; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2024)

Vertical transmission of infectious aerosols through building toilet drainage system: An experimental study - Yuanyuan Niu; Fang Wang; Danting Luo; Zhiyong Shu; Jiayu Huang; Yongpeng Zhang; Cong Liu; Hua Qian (Environmental Pollution, 2024)

Risk evaluation of venue types and human behaviors of COVID-19 outbreaks in public indoor environments: A systematic review and meta-analysis - Weiwei Huang; Caroline X. Gao; Danting Luo; Yong Wang; Xiaohong Zheng; Cong Liu; Ying Wang; Yuguo Li; Hua Qian (Environmental Pollution, 2024)

Exploring user satisfaction and improvement priorities in electric vehicle segments - Danting Zhao; Jie Gao; Nieyangzi Liu (Transportation Research Part D: Transport and Environment, 2023)

Assessing and enhancing urban road network resilience under rainstorm waterlogging disasters - Fei Ma; Yuyun Ao; Xiaojian Wang; Haonan He; Qing Liu; Danting Yang; Huiyan Gou (Transportation Research Part D: Transport and Environment, 2023)

Cerebrospinal Fluid Pressure Reduction Induces Glia-Mediated Retinal Inflammation and Leads to Retinal Ganglion Cell Injury in Rats - Ying Cheng; Danting Lin; Shen Wu; Qian Liu; Xuejing Yan; Tianmin Ren; Jingxue Zhang; Ningli Wang (Molecular Neurobiology, 2023)

The antifungal potential of the chelating agent EDTA against postharvest plant pathogen Botrytis cinerea - Danting Yang; Haojie Shi; Ke Zhang; Xunyue Liu; Liang Ma (International Journal of Food Microbiology, 2023)

Spread of flushing-generated fecal aerosols in a squat toilet cubicle: Implication for infection risk - Danting Luo; Jiayu Huang; Xiaohong Zheng; Fan Liu; Yuguo Li; Ying Wang; Hua Qian (Science of The Total Environment, 2023)

The association of cerebrospinal fluid pressure with optic nerve head and macular vessel density - Xiangxiang Liu; Mohamed M. Khodeiry; Danting Lin; Yunxiao Sun; Qing Zhang; Jiawei Wang; Richard K. Lee; Ningli Wang (Science China Life Sciences, 2022)

Geochemistry of heavy metal-contaminated sediments from the Four River inlets of Dongting lake, China - Xiaohong Fang; Bo Peng; Zhaoliang Song; Sicheng Wu; Danting Chen; Yafang Zhao; Jing Liu; Yanan Dai; Xianglin Tu (Environmental Science and Pollution Research, 2021)

Fine mapping of S32(t), a new gene causing hybrid embryo sac sterility in a Chinese landrace rice (Oryza sativa L.) - Danting Li; Liangming Chen; Ling Jiang; Susong Zhu; Zhigang Zhao; Shijia Liu; Ning Su; Huqu Zhai; Hiroshi Ikehashi; Jianmin Wan (Theoretical and Applied Genetics, 2007)